Low-dose radiation ameliorates doxorubicin-induced renal injury via reducing oxidative stress and protecting mitochondrial function - Mengmeng Chen; Kang He; Kai Wang; Yibo Cai; Zhaohui Ying; Xueting Li; Yating Liu; Liting Xiang; Pingping Yang; Hongjuan Wu; Jian Jiang (PLoS ONE, 2025)
Doxorubicin (DOX) is a well-established chemotherapy drug, but its clinical application is restricted due to significant tissue toxicity, of which nephrotoxicity is a serious adverse reaction. Low-dose radiation (LDR) exerts effects through stimulating diverse cell and molecular mechanisms, which has been shown to have anti-inflammatory and alter immune adaptation effects. This study aims to investigate how LDR protects against DOX-induced nephrotoxicity and to explore the underlying mechanism involved. Sixty mice were randomly divided into control (CTR), LDR, DOX, and combination (COM) group. Nephrotoxicity was induced by injecting a single dose of DOX (7.5 mg/kg) in mice abdominal cavity, and LDR was performed 72 h before DOX treatment. Histological analysis, immunohistochemical analysis, immunofluorescence analysis and western-blotting were used to detect the related indicators. Research data was showed as mean ±SD and tested by One-way ANOVA. The results showed that compared with DOX group, the contents of serum UREA, UA, and the expression level of Bax and caspase 9 were significantly reduced in COM group (P<0.05). Western-blotting and immunohistochemical analysis showed that the expression level of MDA and Nrf2 in COM group were significantly lower than that in DOX group (P<0.05). In addition, the activity of complex Ⅰ, ATP, NDUFA1 and CYC1 were enhanced in COM group compared with DOX group (P<0.05). All the results suggested that LDR pretreatment prevented excessive accumulation of peroxides, restored antioxidants activity (SOD, GSH, CAT), activated Nrf2/HO-1/NQO1 signaling pathway, attenuated damage to the mitochondrial respiratory chain, and protected kidney cells from DOX attack. This study demonstrated that LDR could effectively and safely inhibit the progression of DOX-induced nephrotoxicity. Future studies should further investigate the mechanism of LDR protecting tissues from DOX-induced damage and find an optimal radiation dose for humans.